In Vivo Electroporation of Developing Mouse Retina - de Melo, Jimmy (Methods Mol Biol, 2018)
In vivo electroporation enables the transformation of retinal tissue with engineered DNA plasmids, facilitating the selective expression of desired gene products. This method achieves plasmid transfer via the application of an external electrical field, which both generates a transient increase in the permeability of cell plasma membranes, and promotes the incorporation of DNA plasmids by electrophoretic transfer through the permeabilized membranes. Here we describe a method for the preparation, injection, and electroporation of DNA plasmids into neonatal mouse retinal tissue. This method can be utilized to perform gain of function or loss of function studies in the mouse. Experimental design is limited only by construct availability.